Wall Stroke Training and Precision with Tempo Training on Groundstroke Accuracy Among High School Tennis Students - Nurul Lutfiah; Andi Ihsan; Ahmad Adil (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Groundstroke accuracy is a foundational technical skill in competitive tennis, yet many secondary school student-athletes fail to achieve consistent precision despite adequate stroke mechanics. This study examined the comparative effects of wall stroke training and precision with tempo training on groundstroke accuracy among senior high school tennis students. A quasi-experimental two-group pretest–posttest design was employed. Twenty male students enrolled in the extracurricular tennis program of a senior high school in Makassar City were selected through purposive sampling and randomly assigned to two groups of ten. Both groups underwent a 12-session, four-week structured intervention. Groundstroke accuracy was assessed using the Hewitt Tennis Accuracy Test before and after the intervention. Data were analyzed using paired-sample t-tests for within-group comparisons and independent-sample t-tests for between-group comparisons (α = 0.05). Both training methods produced statistically significant improvements in groundstroke accuracy (p < 0.05). However, the precision with tempo training group demonstrated a significantly greater mean gain (Δ = 6.80 points) compared to the wall stroke training group (Δ = 3.70 points), with the between-group difference confirmed as statistically significant (p < 0.05). These findings indicate that training designs integrating rhythmic control, tempo regulation, and target-based accuracy are more effective than repetitive wall-based practice for improving tennis groundstroke performance in school contexts. The results have practical implications for physical education teachers and extracurricular coaches designing tennis training programs in secondary schools.